2020
DOI: 10.1371/journal.pone.0237872
|View full text |Cite
|
Sign up to set email alerts
|

Altered mastication adversely impacts morpho-functional features of the hippocampus: A systematic review on animal studies in three different experimental conditions involving the masticatory function

Abstract: Recent results have established that masticatory function plays a role not only in the balance of the stomatognathic system and in the central motor control, but also in the trophism of the hippocampus and in the cognitive activity. These implications have been shown in clinical studies and in animal researches as well, by means of histological, biochemical and behavioural techniques. This systematic review describes the effects of three forms of experimentally altered mastication, namely soft-diet feeding, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Furthermore, a meta-analysis of cohort studies found that individuals with <20 teeth were more likely to develop cognitive impairment and dementia, supporting the close correlation between tooth loss and cognitive decline (Cerutti-Kopplin et al 2016). In various animal models of altered mastication, decreases in hippocampal neuron number, synaptic activity, neurogenesis, and spatial memory test performance have been consistently reported (Piancino et al 2020). Thus, disturbed mastication can negatively affect not only the normal function of the hippocampus but also hippocampus-dependent memory and cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a meta-analysis of cohort studies found that individuals with <20 teeth were more likely to develop cognitive impairment and dementia, supporting the close correlation between tooth loss and cognitive decline (Cerutti-Kopplin et al 2016). In various animal models of altered mastication, decreases in hippocampal neuron number, synaptic activity, neurogenesis, and spatial memory test performance have been consistently reported (Piancino et al 2020). Thus, disturbed mastication can negatively affect not only the normal function of the hippocampus but also hippocampus-dependent memory and cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental models of masticatory dysfunction have been explored to clarify the cellular and molecular mechanisms associated with memory impairment [ 25 , 26 , 27 ]. From these studies, we have learned that chewing maintains hippocampus-dependent cognitive function [ 18 ], and that age-related spatial memory deficits can be aggravated by a sedentary lifestyle and a reduction in masticatory activity [ 26 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, a reduction in masticatory activity diminishes neurogenesis and the expression of neurotrophic factor brainderived neurotrophic factor (BDNF) receptors in the dentate gyrus, as well as in the CA1 and CA3 regions of the hippocampus (Fukushima-Nakayama et al, 2017). Thus, abnormal masticatory activity impairs morphofunctional features of hippocampus with synaptic dysfunctional activity, suggesting that all life healthy chewing is essential for hippocampal-dependent cognitive function (Piancino et al, 2020).…”
Section: Introductionmentioning
confidence: 99%